Pseudo-investment scheme in Malaysia: Issues and problems - Muhammad Takiyuddin, Abdul Ghani; Bahyah, Abdul Halim (2017)
Even though the issue of the pyramid and illegal investment scheme has been around since the 90’s, it is still relevant to be highlighted and discussed due to the current increasing list of illegal investment companies and websites which been compiled by Bank Negara Malaysia. The ongoing increasing list has called for more attention from researchers and authorities to be given on this issue. This paper aims to demonstrate some justification on the necessity of conducting this research through library research and pilot study.